Barriers in Collaborative practice among SLP/Ts and Special Educationists Working in Special Education Settings. - Haider, Jamshed; Rehman, Atia ur; Saeed, Bareera; Khan, Muhammad Azzam; Khan, Sikander Ghayas; Naeem, Usra; Malik, Munawar Ahmed; Sutan, Hadia (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
Background: This study was conducted as an attempt to understand the pattern of collaborative behavior and the possible hurdles that Special Education (SE) teachers and school-based Speech-Language Pathologists/Therapists(SLP/Ts) might face, keeping them from efficiently meeting the Speech Language and Communication Needs(SLCN) of individuals in Special Education settings. Objective(s): To investigate the needs of speech and language therapy service in special education settings.. To specify that the particular speech language and communication needs of an individual cannot be sufficiently met by one clinician alone. Methodology: A comprehensive survey questionnaire was employed to attain a clear view of the similarities and differences between the groups of professionals, their understandings of terminology, spoken language indicators of SLCN, associated academic needs, behavioral challenges, and professional barriers to meeting the children’s needs.Results: Fluctuations in the response pattern for both groups were observed when it came to understanding of latest terminologies associated with SLCN, SLP/Ts were predominantly more aware of the terms than special educationists. Special education teachers were unexpectedly more aware of the academic and behavior features related to speech and language difficulties. However, training, advice as well as resource availability saw special educationists lacking whereas slp/ts showed a consistent pattern of having received the necessary training and resources. Conclusion(s): A special education environment is designed to fulfill an individual’s needs, whether they be physical, sensory, cognitive or communicative and to achieve that goal, a compatible team of healthcare professionals and special educators is crucial. In this particular scenario, there is an impending need for both speech language pathologists/therapists and special educators to understand the prerequisites of each other’s role and more importantly how they can assist to provide better Individualized Education Plans(IEPs)(5), improve peer and staff interactions, prevent undesired behavioral interactions, evolve the academic experience and the therapeutic intervention necessary to enhance the quality of life of an individual with speech-language and communication needs.
Keywords: Speech-Language and Communication Needs (SLCN); Special Education teachers; Special Education settings; Multi-professional collaboration.